ILLEGAL LOGGING IMPACT ON THE ENVIRONMENT SUSTAINABILITY IN INDONESIA - Saraha, Abdul Rasyid (Green Earth, 2012)
Indonesias forest is one of the centers of biodiversity in the world, where Indonesia is the third of seven countries called mega diversity country. The high rate of deforestation is causing the failure to achieve forest sustainability. It is reinforced by the presence of illegal logging. Illegal logging is a major cause of deforestation in Indonesia, which reached a level speed of 1.6 - 2.0 million hectares per year. That is why the Ministry of Forestry Indonesia has put the eradication of illegal activity including illegal timber trade. This study was conducted to identify why illegal logging is difficult to stop, and what are the impacts caused by illegal logging on the physical and biotic environment.This study is a literature study and case studies, in order to identify why it is hard to stop illegal logging and also the impacts caused by illegal logging on the physical environment and biotic environment.It is showed that illegal logging is symptoms that arise due to the highly complex issues involving multiple parties from different layers. Illegal logging has become a national issue which the commitment of governments at the national level must be real. However, because this problem occurs at the local level, then the commitment should also be clear areas in which Local Government must have a real responsibility. In general, the problems that led to illegal logging can be grouped into: supply-demand imbalance; government policies that are less precise; multi-dimensional crisis; excesses of decentralization (regional autonomy), and moral forces. A loss due to illegal logging has a broad dimension not only to economic problems, but also to social, cultural, political and environmental. In connection with the problems above , there are some required actions and commitments that must be implemented in an integrated and simultaneously involving the various parties involved stakeholders. Key Word: Illegal logging, Sustainability, Environment